Mapping of Scholarly Output and its Impact Using Open-Source Software - T R, Manu; Garg, Mohit; Hasan, Nabi (Journal of Data Science, Informetrics, and Citation Studies)
Measuring scholarly output has been frequently undertaken to measure the research performance of an institution, journal, or author using the various evaluation techniques and software tools available for analysis and visualization. It has a significant impact on the growth and development of scholarly activities. To provide a platform for professionals/researchers to develop the skills and competencies required for measuring scholarly output, Central Library, IIT Delhi has organized the One Week Workshop on "Mapping of Scholarly Output and its Impact using Open-Source Software" from 22nd -26th May 2023.